Enhanced PCBs sorption on biochars as affected by environmental factors: Humic acid and metal cations - Wang, Yu; Wang, Lei; Fang, Guodong; Herath, H.M.S.K.; Wang, Yujun; Cang, Long; Xie, Zubin; Zhou, Dongmei (Environmental pollution (1987), 2013)
Biochar plays an important role in the behaviors of organic pollutants in the soil environment. The role of humic acid (HA) and metal cations on the adsorption affinity of polychlorinated biphenyls (PCBs) to the biochars in an aqueous medium and an extracted solution from a PCBs-contaminated soil was studied using batch experiments. Biochars were produced with pine needles and wheat straw at 350 °C and 550 °C under anaerobic condition. The results showed that the biochars had high adsorption affinity for PCBs. Pine needle chars adsorbed less nonplanar PCBs than planar ones due to dispersive interactions and separation. Coexistence of HA and metal cations increased PCBs sorption on the biochars accounted for HA adsorption and cation complexation. The results will aid in a better understanding of biochar sorption mechanism of contaminants in the environment. ► Application of the biochars for PCBs sorption was a new and effective way. ► The biochars had higher adsorption affinity for PCBs in the soil extracted solution. ► Pine needle chars adsorbed less nonplanar PCBs than planar ones. ► Coexisting humic acid or metal cations increased PCBs sorption on the biochars. The biochars had higher adsorption affinity for PCBs in the extracted soil solution because coexisting humic acid and metal cations increased their sorption.